THE ANALYSIS OF FIGURATIVE LANGUAGE IN SAHEEH INTERNATIONAL TRANSLATION OF SOME VERSES OF AL – QUR’AN DEALING SEX RELATION - Rosyidah, Rossy Halimatun; Meylinda, Linda (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2023)
Talking about sex is a taboo because there are understanding that sex is dirty and porn. In case, what if sex is spoken by the Scriptures? Al-Qur’an and Bible discuss it. This research focuses on the verses of Al-Qur’an. There are some surahs of Al Qur’an explain about sexual relations : Al â€“ Aâ€™raf verse 189, Al â€“ Baqarah 187, 222,223,236,237, Mujadallah 3, 4, Ali Imran 47, An Nisa 21, 23, and Maryam 20. These verses have interesting meanings to study with semantics approach because language in Al-Qur’an has literal and figurative meanings. Literal language, words are employed to convey meaning as defined, while figurative language is words are employed to provide room for interpretation. In the Al Quran, there are some verses that need more explanation or display in figure context; one example in verses that explain about sex relation. Therefore, the problem of this research is what are the figurative languages used in some verses of Al Qur’an dealing sex relation which translate by Saheeh International and what does the utilized figurative language mean? This study is aimed to analyze figurative language described in some verses of Al-Qur’an dealing marital sex which translate by Saheeh International and to know what is the meaning of figurative language used. The benefit of study is giving information to get knowledge about figurative language. This research employed a qualitative approach using document analytical methods. The data collected from Saheeh International translation. In analyzing the data used McArthur theory. Then the result there are 3 kinds different of figurative language found; Metonymy is replacing word with another word that has a meaning close to the original word, metaphor is describing things in a way that the reader can visualize, euphemism is replacing a word or phrase with another in order to make the sentence sound more polite and soft. Keyword: Figurative Language, Al Qur’an Translation, Semantics